(untitled) (American Journal of Islam and Society, 2019)
Analytic theologians seem to unreservedly prioritise a realist view in the way they approach theological dogmas. I have previously argued that this particular type of realist methodological approach that is adopted by most analytic theologians is inconsistent with the Islamic tradition. I demonstrated that this inconsistency lies between two primary theses which constitute realism and an absolutely transcendent and ineffable God of the Islamic tradition. I had established how each of these theses proved responsible, in different ways, for divesting the Islamic God of His absolute transcendence. In this paper I determine why this is the case. I primarily seek to explicate the underlying reason for why metaphysical (theological) realism proves to be responsible for stripping the Islamic God of His absolute transcendence. This would involve being able to stipulate, somewhat accurately, the precise source of the accentuated inconsistency between metaphysical (theological) realism and the Islamic understanding of an absolutely transcendent and ineffable God. The exact source of this inconsistency, I shall argue, is grounded in Quine’s ontological theses which underlie much of what metaphysical realism imports into the domain of analytic theology.